Surface characterization of nanoparticles: different surface analytical techniques compared. (18th July 2012) - Kersting, R.; Breitenstein, D.; Hagenhoff, B.; Fartmann, M.; Heller, D.; Grehl, T.; Brüner, P.; Niehuis, E.
<x xml:space="preserve">Abstract</x> The rapidly growing interest in nanoparticles (NPs) as part of technical products conflicts with the limited knowledge about potential health risks. This dilemma is the initial point of the project NanoPaCT1 where, based on the chemical composition of NPs and toxicological tests, a forecast on their biological activity should be made. For the chemical characterization of the outer surface of core‐shell NPs, an excellent surface sensitivity of the applied analytical techniques is required. In this article, we will present data on an approach to optimise time‐of‐flight secondary ion mass spectrometry (ToF‐SIMS) to this need. The effect of primary ion parameters (species, energy) was studied on a model system (HfO2 on Si) as well as on Lumidot core‐shell NPs. The full layer closure of both films was proofed by means of low energy ion scattering. On the flat high‐K sample, a clear variation of surface sensitivity could be observed as function of primary ion (PI) parameters. In contrast to this, almost no effect was found on core‐shell NPs which behave in the experiment like homogeneous particles. These results indicate that NPs probably melt‐up or evaporate after direct or grazing impact of PI at typical energies used in ToF‐SIMS. Copyright © 2012 John Wiley & Sons, Ltd.